MLVA25-Typed Yersinia pestis ssp. central asiatica biovar altaica Genotype Structure in Gorno-Altai Mountain Natural Plague Focus - M. B. Yarygina; V. M. Korzun; S. V. Balakhonov; E. N. Rozhdestvensky; A. V. Denisov (Проблемы особо опасных инфекций, 2021)
The aim of the work was to study the genetic diversity and spatial-temporal genotype structure of Yersinia pestis subspecies central asiatica biovar altaica in the Gorno-Altai natural plague focus, using MLVA25-typing.Materials and methods. MLVA25-typing of 330 strains of Y. pestis ssp. central asiatica bv. altaica, isolated in the Gorno-Altai mountain natural plague focus during 1961–2015 was carried out. The phylogenetic tree was constructed with the help of UPGMA and MST algorithms.Results and discussion. The analyzed strains have been differentiated into 34 MLVA types based on cluster analysis. The formed major groups of strains show pronounced spatial confinedness. Three chorological groupings of the plague agent with peculiar genotype characteristics have been identified. Each of the groupings is circulating among the main carrier (Ochotona pallasi) population and within the limits of the similarly-named mesofocus, respectively (Ulandryksky, Tarkhatynsky and Kuraisky). MLVA25 structure of Y. pestis in Ulandryksky and Kuraisky mezofoci show stability over time; there are no significant changes from the time of their first detection in 1961 and 1999, respectively. The dramatic changes in MLVA25 structure are observed in Tarkhatynsky mesofocus, which is known from 1972. Mass expanding of the MLVA25 types which were very rare before took place there from the beginning of 1990-s, along with elimination of the types absolutely dominant up to 1980s. Most likely the changing of dominating genotypes is attributable to the bottleneck effect, arising from the sharp decline of the focal epizootic activity in the mid 1980s.